Genomic regions associated with resistance to anthracnose in the Guatemalan climbing bean (Phaseolus vulgaris L.) germplasm collection - C. R. Maldonado-Mota; S. M. Moghaddam; S. Schröder; O. P. Hurtado-Gonzales; P. E. McClean; J. Pasche; R. Lamppa; M. A. Pastor-Corrales; M. G. Tobar-Piñón; J. M. Osorno (Genetic Resources and Crop Evolution, 2021)

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

Mapping and characterization of two stem rust resistance genes derived from cultivated emmer wheat accession PI 193883 - Jyoti S. Sharma; Qijun Zhang; Matthew N. Rouse; Daryl L. Klindworth; Timothy L. Friesen; Yunming Long; Pablo D. Olivera; Yue Jin; Phillip E. McClean; Steven S. Xu; Justin D. Faris (Theoretical and Applied Genetics, 2019)

Genetic analysis of threshability and other spike traits in the evolution of cultivated emmer to fully domesticated durum wheat - Jyoti S. Sharma; Katherine L. D. Running; Steven S. Xu; Qijun Zhang; Amanda R. Peters Haugrud; Sapna Sharma; Phillip E. McClean; Justin D. Faris (Molecular Genetics and Genomics, 2019)

Evidence gaps and biodiversity threats facing the marine environment of the United Kingdom’s Overseas Territories - Bethan C. O’Leary; Philip Fieldhouse; Colin J. McClean; Adriana E. S. Ford; Polly Burns; Julie P. Hawkins; Callum M. Roberts (Biodiversity and Conservation, 2019)

Extremely short duration interval exercise improves 24-h glycaemia in men with type 2 diabetes - Richard S. Metcalfe; Ben Fitzpatrick; Sinead Fitzpatrick; Gary McDermott; Noel Brick; Conor McClean; Gareth W. Davison (European Journal of Applied Physiology, 2018)

An undercurrent off the east coast of Sri Lanka - Arachaporn Anutaliya; Uwe Send; Julie L. McClean; Janet Sprintall; Luc Rainville; Craig M. Lee; S. U. Priyantha Jinadasa; Alan J. Wallcraft; E. Joseph Metzger (Ocean Science, 2017)
The existence of a seasonally varying undercurrent along 8° N off the east coast of Sri Lanka is inferred from shipboard hydrography, Argo floats, glider measurements, and two ocean general circulation model simulations. Together, they reveal an undercurrent below 100–200 m flowing in the opposite direction to the surface current, which is most pronounced during boreal spring and summer and switches direction between these two seasons. The volume transport of the undercurrent (200–1000 m layer) can be more than 10 Sv in either direction, exceeding the transport of 1–6 Sv carried by the surface current (0–200 m layer). The undercurrent transports relatively fresher water southward during spring, while it advects more saline water northward along the east coast of Sri Lanka during summer. Although the undercurrent is potentially a pathway of salt exchange between the Arabian Sea and the Bay of Bengal, the observations and the ocean general circulation models suggest that the salinity contrast between seasons and between the boundary current and interior is less than 0.09 in the subsurface layer, suggesting a small salt transport by the undercurrent of less than 4 % of the salinity deficit in the Bay of Bengal.

Navigating the complexity of ecological stability - Ian Donohue; Helmut Hillebrand; José M. Montoya; Owen L. Petchey; Stuart L. Pimm; Mike S. Fowler; Kevin Healy; Andrew L. Jackson; Miguel Lurgi; Deirdre McClean; Nessa E. O'Connor; Eoin J. O'Gorman; et al. (Ecology Letters, 2016)
Human actions challenge nature in many ways. Ecological responses are ineluctably complex, demanding measures that describe them succinctly. Collectively, these measures encapsulate the overall ‘stability’ of the system. Many international bodies, including the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, broadly aspire to maintain or enhance ecological stability. Such bodies frequently use terms pertaining to stability that lack clear definition. Consequently, we cannot measure them and so they disconnect from a large body of theoretical and empirical understanding. We assess the scientific and policy literature and show that this disconnect is one consequence of an inconsistent and one‐dimensional approach that ecologists have taken to both disturbances and stability. This has led to confused communication of the nature of stability and the level of our insight into it. Disturbances and stability are multidimensional. Our understanding of them is not. We have a remarkably poor understanding of the impacts on stability of the characteristics that define many, perhaps all, of the most important elements of global change. We provide recommendations for theoreticians, empiricists and policymakers on how to better integrate the multidimensional nature of ecological stability into their research, policies and actions.

A critical re-evaluation of controls on spatial and seasonal variations in nitrate concentrations in river waters throughout the River Derwent catchment in North Yorkshire, UK - Shaheen Begum; Muhammad Adnan; Colin J. McClean; Malcolm S. Cresser (Environmental Monitoring and Assessment, 2016)

New QTL alleles for quality-related traits in spring wheat revealed by RIL population derived from supernumerary × non-supernumerary spikelet genotypes - Morgan Echeverry-Solarte; Ajay Kumar; Shahryar Kianian; Senay Simsek; Mohammed S. Alamri; Eder E. Mantovani; Phillip E. McClean; Edward L. Deckard; Elias Elias; Blaine Schatz; Steven S. Xu; Mohamed Mergoum (Theoretical and Applied Genetics, 2015)

Investigation of the multifaceted iron acquisition strategies of Burkholderia cenocepacia - J. Tyrrell; N. Whelan; C. Wright; I. Sá-Correia; S. McClean; M. Thomas; Máire Callaghan (BioMetals, 2015)

Obesity and head and neck cancer risk and survival by human papillomavirus serology - Xinmiao Tan; Heather H. Nelson; Scott M. Langevin; Michael McClean; Carmen J. Marsit; Tim Waterboer; Michael Pawlita; Karl T. Kelsey; Dominique S. Michaud (Cancer Causes & Control, 2015)

Co-segregation analysis and mapping of the anthracnose Co-10 and angular leaf spot Phg-ON disease-resistance genes in the common bean cultivar Ouro Negro - M. C. Gonçalves-Vidigal; A. S. Cruz; G. F. Lacanallo; P. S. Vidigal Filho; L. L. Sousa; C. M. N. A. Pacheco; P. McClean; P. Gepts; M. A. Pastor-Corrales (Theoretical and Applied Genetics, 2013)

Periodontal disease and mouthwash use are risk factors for head and neck squamous cell carcinoma - Melissa N. Eliot; Dominique S. Michaud; Scott M. Langevin; Michael D. McClean; Karl T. Kelsey (Cancer Causes & Control, 2013)

Regular dental visits are associated with earlier stage at diagnosis for oral and pharyngeal cancer - Scott M. Langevin; Dominique S. Michaud; Melissa Eliot; Edward S. Peters; Michael D. McClean; Karl T. Kelsey (Cancer Causes & Control, 2012)

Allergies and risk of head and neck cancer - Dominique S. Michaud; Scott M. Langevin; Melissa Eliot; Heather H. Nelson; Michael D. McClean; Brock C. Christensen; Carmen J. Marsit; Karl T. Kelsey (Cancer Causes & Control, 2012)

Linkage mapping of the Phg-1 and Co-1 4 genes for resistance to angular leaf spot and anthracnose in the common bean cultivar AND 277 - Maria Celeste Gonçalves-Vidigal; Anelise S. Cruz; Alexandre Garcia; J. Kami; Pedro S. Vidigal Filho; Lorenna L. Sousa; P. McClean; P. Gepts; M. A. Pastor-Corrales (Theoretical and Applied Genetics, 2011)

Role of lipase in Burkholderia cepacia complex (Bcc) invasion of lung epithelial cells - T. Mullen; K. Markey; P. Murphy; S. McClean; M. Callaghan (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Comparison of antibiotic susceptibility of Burkholderia cepacia complex organisms when grown planktonically or as biofilm in vitro - E. Caraher; G. Reynolds; P. Murphy; S. McClean; M. Callaghan (European Journal of Clinical Microbiology & Infectious Diseases, 2007)